(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2023)
In the present paper the application of Laplace transform and its inverse transform, for solving ordinary differential equation with constant coefficients and initial condition is considered. The solution of ordinary differential equation that describes serial RLC circuit is provided. Some results of the simulations are also given.